Influence of Pt doping on the sensing mechanism of La2O3/SnO2 thick film for CO2 gas - Ehsani, Maryam; Hamidon, Mohd Nizar (Australian International Academic Centre, 2014)
Thick film CO2 sensors were fabricated using La2O3/SnO2 loaded with Pt and in the unloaded form. The nano-crystalline powders of SnO2-La2O3-Pt synthesized by high speed ball milling method were screen-printed on alumina substrates. The resistance of fabricated sensors were measured against different CO2 concentration in the working temperature of 225 C. The composition that gives an acceptable resistivity for CO2 was in the 3wt.% ratio of Pt.